Auditor independence judgments: A cognitive‐developmental model and experimental evidence* - PONEMON, LAWRENCE A.; GABHART, DAVID R.L. (Contemporary Accounting Research, 1990)
Abstract. This paper describes a psychological framework that examines auditors' conceptions of independence in the context of ethical cognition. An experimental study of independence judgments of 119 partners and managers in two national public accounting firms is reported. Using a well‐known measure of ethical cognition, this study examines auditors' implicit reasoning in the resolution of an independence paradigm. The most significant are that (1) a systematic relationship between auditors' measured ethical cognition and their resolution of an independence conflict exists, (2) the penalty attribute is a much stronger influence than the affiliation attribute on the auditors' ethical resolve, and (3) the cognitive measure used in this study can be used efficiently to explain priority rankings of a majority of independence attributes developed in earlier research. Résumé. Les auteurs décrivent ici une grille psychologique permettant d'analyser la façon dont les vérificateurs conçoivent l'impartialité dans le contexte de la conscience éthique. Ils font état des résultats d'une étude expérimentale des jugements d'impartialité de 119 associés et chefs de groupe attachés à deux cabinets d'experts‐comptables nationaux. Utilisant une mesure bien connue de la conscience éthique, les auteurs ana‐lysent le raisonnement implicite des vérificateurs dans la résolution d'un paradigme d'impartialité. Les principaux résultats de l'étude sont les suivants: 1) il existe une relation systématique entre la conscience éthique mesurée chez les vérificateurs et la façon dont ils résolvent un problème d'impartialité, 2) l'attribut « sanction » a sur la décision éthique des vérificateurs une influence beaucoup plus grande que l'attribut « affiliation » et 3) la mesure cognitive utilisée dans cette étude est efficace dans l'explication des classements de la plupart des attributs d'impartialité définis dans le travaux de recherche antérieurs.